ANALISIS PERBANDINGAN KINERJA KEUANGAN MENGGUNAKAN METODE CAMEL PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ika Dian Aruna; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the comparison of the financial performance of State-Owned Corporation (SOE) Banks listed on the Indonesia Stock Exchange (IDX) in the 2015-2020 period. In its application, the researcher used the CAMEL method through the ratios of CAR, KAP, NPM, ROA, BOPO, and LDR, and found out the evaluation results of the CAMEL method to assess the soundness of a bank during the 2015-2020 period by the provisions of SE BI No.6/23/DPNP in 2004. The object of this study is data from SOE Banks for 2014-2020 obtained from the website www.idx.co.id and the website of each bank. The results showed that the health level of Bank Rakyat Indonesia (BRI) and Bank Mandiri were in the healthy predicate, while Bank Negara Indonesia (BNI) and Bank Tabungan Negara (BTN) were in the fairly healthy predicate. Keywords: Comparison Of The Financial Performance, CAMEL.